(untitled) (Scientific journal of the Fergana State University, 2024)
This article tells about the Landscape Map, about the division of its appearance into species, about the importance of their use, what will be relied on in the prediction of landscapes, what information will be concentrated in it, various variations are described through the North Fergana mountain landscapes map.